STRATEGI PROMOSI DIGITAL UMKM NAGA DIMSUM SURABAYA MELALUI MEDIA SOSIAL INSTAGRAM - Aliza Naomi Nuraini; Inge Novalia; Aishya Syahdabila Fahira; Halimah (PT. Hasba Edukasi Mandiri, 2025)
The advancement of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adapt their marketing strategies to remain competitive in the modern era. Naga Dimsum Surabaya, a local culinary MSME, still faces challenges in optimizing social media particularly Instagram as an effective and sustainable promotional tool. This community service program aims to enhance digital marketing capacity through training and mentoring activities focused on Instagram management. A qualitative descriptive approach was applied using a case study on the Instagram account @nagadimsum.sby, involving young participants, especially Generation Z, as the primary target group. The training materials emphasized creative content development, posting schedule management, and audience engagement analysis to improve digital interaction. The results indicated an increase in participants’ knowledge, skills, and awareness in designing attractive and effective promotional strategies. Overall, this activity contributes to empowering MSMEs by strengthening their digital competence while promoting sustainable business practices and youth participation in the creative economy.